2013
DOI: 10.1103/physreva.88.063409
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polarization-averaged molecular-frame photoelectron angular distributions and geometry

Abstract: We present a theoretical study of vibrationally resolved and unresolved molecular-frame photoelectron angular distributions (MFPADs) resulting from K-shell photoionization of N 2 , CO, C 2 H 2 , NH 3 , CH 4 , CF 4 , BF 3 , and SF 6 in the range of photoelectron energies 0-500 eV. We show that the MFPADs of NH 3 and CH 4 , averaged over the polarization direction, image the molecular geometry at very low energies but also at selected higher energies. For all other molecules, the MFPADs do not image the system's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…While the polarization-averaged MFPAD clearly reflects the symmetry of the target molecule, the pattern of preferential photoelectron emission contrasts sharply with that found for ethane (and methane). In this case, the photoelectron emission peaks between the fluorines, in line with findings previously reported [6,12] that suggest the opposite of the imaging effect in this molecule.…”
Section: Carbon Tetrafluoridesupporting
confidence: 92%
See 2 more Smart Citations
“…While the polarization-averaged MFPAD clearly reflects the symmetry of the target molecule, the pattern of preferential photoelectron emission contrasts sharply with that found for ethane (and methane). In this case, the photoelectron emission peaks between the fluorines, in line with findings previously reported [6,12] that suggest the opposite of the imaging effect in this molecule.…”
Section: Carbon Tetrafluoridesupporting
confidence: 92%
“…For example, measurements of the MFPADs at low energies for the methane molecule [8] reveal a dramatic apparent "imaging" of the molecular geometry, in the sense that when averaged over polarization directions, both measured and calculated MFPADs showed a strong tendency for an electron ionized from the carbon 1s level to be ejected along the direction of the bonds in the molecule. Subsequent theoretical calculations demonstrated that polarization averaged MFPADs show this "imaging" effect in some cases [5] but not in others [3,6]. In fact, the opposite behavior, which might be called "anti-imaging", is also seen in calculations of MFPADs for some molecules in which the ejected core electron seems to be directed away from the directions of bonds in the molecule [6] in an energy-dependent effect that has been interpreted in terms of the chemical electronegativity of the atomic species involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such investigations have mainly addressed the localized K-edge ionization of diatomic [7][8][9][10][11] and triatomic [12,13] molecules in the vicinity of shape resonances. Only very recently have such case studies extended to consider PADs in larger non-linear polyatomics [14] and/or valence shell ionization. [11,15] There remains, in any case, little evidence to indicate notable vibrational influence on molecular PADs in regions removed from continuum resonances, other than a near threshold, K-edge study of fixed-in-space CO. [16,17] Set against this background, a suggestion of a vibrational dependency in the non-resonant outer valence electron PAD of methyloxirane [18] was interesting and stimulated a further PECD investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[18] have recently reported C (I s -1) MFPADs for HCCH obtained from static-exchange density functional calculations. Their results differ markedly from ours.…”
Section: Results Of Carbon-a-shell Photoionizationmentioning
confidence: 99%